Prevalence and Related Risk Factors of Intestinal Parasitosis among Private School-Going Pupils of Dharan Submetropolitan City, Nepal - Bijay Kumar Shrestha; Manita Tumbahangphe; Jenish Shakya; Anu Rai; Kabita Dhakal; Bidhya Dhungana; Romika Shrestha; Jyoti Limbu; Kabiraj Khadka; Santoshi Ghimire; Sujata Chauhan; Lata Chalise; et al. (Journal of Parasitology Research)
Introduction. Intestinal parasitic infections are most common and prevalent among children and accounts for great morbidity and mortality. Objective. This research is aimed at studying the prevalence and related risk factors of parasitic infections among private school-going pupils of Dharan Submetropolitan City. Methods and Materials. This was a cross-sectional laboratory-based study conducted from 13 November 2018 to 26 February 2019 among 400 private school pupils. The stool samples were collected and microscopically examined for parasites using the formalin ethyl acetate sedimentation technique. Data Analysis. Statistical analysis was performed by using SPSS version 16.0. Pearson’s Chi-square test was used to establish association between dependent and independent variables. The association was also determined using crude and adjusted odds ratio, and the test considered a P value < 0.05 as statistically significant with 95% confidence interval. Result. In this study, 46 (11.5%) children were positive for intestinal parasites. In this study, 3 protozoans (Entamoeba histolytica = 3 (0.75%)) and 43 helminths (Ascaris lumbricoides = 22 (5.5%); Enterobiusvermicularis = 6 (1.5%); Ancylostoma duodenale = 2 (0.5%); and Trichuris trichiura = 13 (3.25%)) were isolated and identified. Statistically, significant difference in the parasitic prevalence with respect to age and gender was not seen (P>0.05). However, the prevalence of parasitic infection was strongly associated with the ethnicity of the pupils (P=0.001). The strong associated risk factors of intestinal parasitic infections were nail-biting habit, source of drinking water, biannual deworming, thumb-sucking, hand sanitation before having food and after toilet, knowledge of parents on parasitosis, health and sanitation, keeping cat/dog as pet, and wearing protective shoes during play (P=0.001). Bowel syndromes like abdominal cramp and constipation also had a strong statistical association (P=0.001) with the prevalence of parasitic infection. According to binary and multivariate logistic regression analyses, the parents without awareness, pupils with a nail-biting habit, pupils not wearing shoes during play, lack of deworming, drinking direct tap water, and pupils with poor hand sanitation were more likely to be infested with intestinal parasitic infections. Conclusion. This study concludes that intestinal parasites are still prevalent among private school-going pupils of Dharan Submetropolitan City. The poor sanitation and sanitary habits like biting nails, consumption of untreated drinking water, and failure to practice proper hand washing were studied as contributors to the acquisition of intestinal parasitic infections. Therefore, integration of control measures such as provision of clean and safe drinking water, improved sanitation and hygiene, with biannual administration of drugs are necessary for effective eradication of parasitic infections.